Factores protectores o de riesgo de la satisfacción con la vida adultos mayores. Zona 7 - Ortega Villamagua, Robert Augusto (2017)
A quantitative, transverse and correlational study was carried out in zone 7 of Ecuador. The universe was made up of all people 65 and over. Sampling was stratified randomly by dividing the population into subgroups or strata that have some common characteristic, conditioning by an expected frequency of 50%, 95% confidence interval, design defect 0.1 and establishing a clutter for each province. The sample was made up of 1146 older adults distributed as follows: Loja 395, El Oro 385 and Zamora Chinchipe 366. A survey was carried out using an instrument designed for this study, which collected sociodemographic data. The Life Satisfaction Scale of Diener and Lopez was applied, which became 27.2% of the total population studied. Concluding that satisfaction with life, measured by the Diener Scale, with work status and retirement are related, with a predominance of those who have no work and those who are retired, in addition to an increase of those who do not receive the bonus and do not have chronic diseases. Using the modified Diener Scale for this study, marital status, receiving the bonus, diabetes mellitus, heart disease, musculoskeletal diseases, and family functioning behaved as a risk factor for older adults. Keywords. Satisfaction with life, Older adults, Protective factors.